The pattern of association between histopathological vs clinical and radiological findings of lung cancer biopsy in patients of lung cancer - Syed Naeem Raza Hamdani, Ayesha Anwar, Faiza Khan, Nasim Aslam Ghumman, Farukh Bashir, Amna Mubeen (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Lung cancer is one of the most deadly tumours known. It is accurately found by many radiographic testing methods occasionally initiated for an unrelated ailment. In light of new histology guided therapeutic modalities and lung cancer genetic categorization, histological characterisation of lung cancer has risen in prominence. Aim: To link histology findings with clinical and radiographic features. Methods: This prospective investigation followed 40 patients with suspected lung cancer for a year, looking at clinical, radiological, and histological features. The research covered a clinical history, smoking habits, full physical examination of the respiratory system, chest roentgenogram, computed tomography of the thorax, fiberoptic bronchoscopy, and others. Results: Patients were aged 56.7 years with 80.2% male and 19.8% female. The most frequent symptom was cough 84.6%. Lesion 85.5% followed by collapse consolidation 35.26% were the most frequent radiological results. Squamous cell carcinoma most typically showed as a hilar mass 54.4%, adenocarcinoma as a peripheral mass 67.4%. Squamous cell carcinoma 48% was the most frequent form, followed by small cell carcinoma 13% and adenocarcinoma 2.98% . Conclusion: In order to confirm a clinical or radiological diagnosis of lung cancer, endobronchial lung biopsy and histopathology are both extremely necessary tests to do.